Global Health and Public Health Majors and Minors at 411 Universities, 2019–2020 - Caryl E. Waggett (Ubiquity Press, 2020)
Background: There has been rapid growth in the popularity of undergraduate degrees in global and public health, but that growth has not been evenly distributed across different types of institutions of higher education. Objective: To examine the prevalence of undergraduate global and public health majors and minors and related degrees at a diversity of higher education institutions in the United States during the 2019–20 academic year. Methods: We examined curricular offerings at the top 100 national universities, national liberal arts colleges, regional universities, and regional colleges included in the 2020 U.S. News and World Report rankings. With ties, the dataset included 411 of the 1600 ranked U.S. colleges and universities. Findings: In total, 101 (25%) of the 411 schools offer a general public health, community health, or global health major, 105 (26%) a minor, and 144 (35%) a major and/or minor. When subdisciplines and other population health related programs are included, 160 (39%) offer a major, 183 (45%) a minor, and 227 (55%) a major and/or minor, including 83% of national universities, 57% of regional universities, 45% of national liberal arts colleges, and 35% of regional colleges. Global health programs, usually minors, are offered by 32% of national universities and 8% of national liberal arts colleges. Conclusions: Global and public health have become common areas of primary and secondary study at the bachelor’s level at diverse schools in the United States. Although these degree pathways are especially prevalent at large urban universities, schools of all sizes, types, and locations have invested in offering educational programs in population health areas.